Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Untuk Meningkatkan Keaktifan Belajar Peserta Didik SMA Negeri 14 Medan - Pesta Rut Cahaya Sitanggang; Saiful Bahri; Dedy Juliandri Panjaitan; Evi Julyana Nasution; Rennika Irfenti Seprina Simorangkir (Departement of Mathematics Education, 2024)
As the less from disciples of participate study that begin from problem that background for this research. The purpose of the act class is research what if apply cooperative model from type of Teamn Games Tournament (TGT) that could increase teh Interactive stude from disciples. This research that used descriptive kuantitative method with collecting result from observatio, kuesioner and documentary. The result from research show that score average for whole of indicator that take from disciples beside siklus 1 is 74,7 with passive criteria that 3 people, and the active criteria most active is 14 people. The persentage that reach from first siclus is 72,5 ℅. For applying from the second siclus, that reach from the disciples with the active of criteria that 13 people, and the most active that 21 people. Average score that reach for all disciples that 82,7%. For the active percentage study as the indicator is 87,9℅. From. The observation result and kuetioner that done, the learning with TGT Model for increase the stude active for this research, that reach increasing with amount of the active of disciples and most active for Siclus 1 for Siclus from 31 people become 34 people.